Research Development on Management of Child-Friendly Schools (CFS) in Elementary School: A Bibliometric Analysis Using VOSviewer - Suherman, Irman; Adri, Helmia Tasti; Muttaqien, Agung; Kholik, Abdul; Hayu, Wiworo Retnadi Rias (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to analyze the research trends development of management on child-friendly schools (CFS) management at the elementary school. The research method used is bibliometric analysis. Data was obtained from the Google Scholar database in the form of papers published in international journals from 2017-2022. Data processing was carried out in three stages, 1) data collection, 2) data selection and 3) data analysis using VOSviewer. The results showed that the trend of research development on management of child-friendly school was highest in 2013 with 162 publications. The results of the overlay analysis shown in yellow circles indicate research topics that are often used in recent research, namely young child, early childhood education, children, appropriate education, need, school closure, learning, pandemic, covid, parent and home. While topics that are rarely used are clinician, school climate, school closure, disability, anxiety, autism spectrum disorder, women. The results of this study illustrate that the research topic for management of child-friendly school can be developed towards the term model of friendly schools for women and disabilities, development of a child-friendly school climate, and friendly schools for children with special needs.